PERAN PEMERINTAH DESA TERHADAP PENGAWASAN LARANGAN PENGGALIAN PASIR TANPA IZIN - Duha, Sindi Dewintasari (JURNAL PANAH KEADILAN, 2025)
Indonesia is a country of law, meaning that actions carried out in national and state life must be regulated in accordance with the law. The village government is a government institution tasked with managing village-level areas, where the village head and assisted by village officials are the organizing elements of village government. Prohibition is an order or rule that regulates an action. Excavation of sand without a permit is excavation below the surface of the land either on land or under riverbeds with the intention of returning non-metallic mineral minerals (sand) which have economic significance which is carried out without having a permit. The case in Ganowo Saua Village is the role of the Village Government in supervising the prohibition on excavating sand without a permit. The type of research used in this research is sociological research. Data collection was carried out by interviews and document study. The data analysis carried out was descriptive qualitative analysis and conclusions were drawn using a deductive method. Based on research findings and discussion, it can be concluded that the reason for sand excavation is because of economic problems and the lack of employment opportunities. Excavating sand is detrimental to other communities by causing landslides in areas of people's houses which destroy the walls dividing people's houses and the sea. The role of the Ganowo Saua Village government is only to convey the prohibition verbally to the community. The author suggests that the community no longer digs sand without permission, the village government must be firm and active and collaborate with the local government in supervising and taking action against sand diggers through outreach and going directly to the field by following Regional Regulation Number 11 of 2008 concerning Retribution for Material Mining Business Permits. Class “C” Excavations in South Nias Regency.